NOVITATES GABONENSES 68. THE GENUS CASSIPOUREA (RHIZOPHORACEAE) IN CONTINENTAL TROPICAL AFRICA WITH EMPHASIS ON GABON: SUBGENERIC DIVISION, IDENTIFICATION KEYS, AND DESCRIPTION OF TWO NEW SPECIES - Breteler, F. J. (Edinburgh Journal of Botany, 2008)
Cassipourea (Rhizophoraceae) is represented in Gabon by 11 species, of which C. nana Breteler and C. ndambiana Breteler are described as new and C. carringtoniana Mendes, C. gummiflua Tul. and C. ruwensorensis (Engl.) Alston are reported from this country for the first time. The subgeneric classification is discussed. An adapted key to the subgenera and a key to the Gabonese species is presented. A synopsis of the subgenera and of the Gabonese species is also given. The new species and Cassipourea carringtoniana are fully illustrated. A few illustrations of some other species to elucidate characters of the subgenera are provided.